Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Perilaku Pengelolaan Keuangan pada Mahasiswa Akuntansi Universitas 17 Agustus 1945 Surabaya - Diana Indah Sri Lestari P. A; Hwihanus Hwihanus (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This study aims to analyze the influence of financial literacy and lifestyle on the financial management behavior of accounting students at the University of 17 August 1945 Surabaya. The research uses a qualitative approach, collecting data through open-ended questionnaires distributed to five students. The results show that financial literacy plays a significant role in helping students manage their finances, such as prioritizing academic needs and saving. However, a consumptive lifestyle influenced by social media can pose challenges in financial management, especially when students are more influenced by trends than the financial knowledge they possess. This study concludes that the development of financial literacy programs among students is necessary to promote healthy financial habits and achieve better financial well-being.